Peran Guru Dalam Pengelolaan Kelas Terhadap Hasil Belajar Siswa di SDN 1 Kayangan Kabupaten Lombok Utara - Jannah, Rauhun (Lembaga Penelitian dan Pendidikan Mandala, 2023)
In order for educators to develop innovative learning activities, they must have the skills and strive for their development. One of the eight basic teaching skills is variety. This study aims to find out how the teacher's ability influences variations in classroom management. The author of this study conducted research using the library method, namely reading books, articles, and relevant journals as well as data sources. The results showed that increasing student interest in learning, improving student learning outcomes, increasing student achievement, and improving student learning achievement all have a significant effect on the teacher's ability to manage the class. active involvement and motivation of student learning. Consequently, teachers should concentrate on increasing their capacity to manage classroom variation.